2020
DOI: 10.1111/hsc.12919
|View full text |Cite
|
Sign up to set email alerts
|

Informal carers' experiences of caring for a person with heart failure in a community setting

Abstract: Heart failure (HF) is a life‐limiting condition with a poor prognosis and unpredictable disease trajectory. HF brings physical and emotional challenges for patients and their carers. Predominantly the informal carer population consists of older females, however, caring is evolving as longevity increases and complex conditions are becoming more commonplace. Consequently, more men and younger people are contributing to daily care. The aim of this study was to explore the positive as well as negative dimensions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…25 In this regard, numerous recent studies have highlighted challenges experienced by caregivers of patients with HF. [37][38][39][40] Some initiatives along these lines, such caregiver-specific QoL questionnaires, 41 and video coaching, 42 43 are currently being developed and tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In this regard, numerous recent studies have highlighted challenges experienced by caregivers of patients with HF. [37][38][39][40] Some initiatives along these lines, such caregiver-specific QoL questionnaires, 41 and video coaching, 42 43 are currently being developed and tested.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, these results suggest that instruments should be developed to help caregivers in their daily work with patients with HF, so that they are better informed on the course of the disease and expectations 25. In this regard, numerous recent studies have highlighted challenges experienced by caregivers of patients with HF 37–40. Some initiatives along these lines, such caregiver-specific QoL questionnaires,41 and video coaching,42 43 are currently being developed and tested.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have found that FCGs-HF neglect their health needs since the caregiving role affects them physically and mentally and affects their ability to plan physical activities. 29 Moreover, if FCGs of persons with heart failure do not have an established level of selfefficacy based on a history of PA, positive beliefs of competence, or a strong motivation for PA, then lack of self-efficacy could be a barrier to engaging in PA. 30 This study has limitations and strengths that need to be mentioned. First, recruiting participants at a single academic medical center with a convenience sample of predominately female, white, and non-Hispanic FCGs limits generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have found that FCGs-HF neglect their health needs since the caregiving role affects them physically and mentally and affects their ability to plan physical activities. 29 Moreover, if FCGs of persons with heart failure do not have an established level of self-efficacy based on a history of PA, positive beliefs of competence, or a strong motivation for PA, then lack of self-efficacy could be a barrier to engaging in PA. 30…”
Section: Discussionmentioning
confidence: 99%
“… 1 Both terms are used interchangeably throughout this paper. While some positive aspects of providing care have been reported by care partners, including a sense of giving back or reciprocity (e.g., in the case of caring for a parent), and as a continued part of a loving relationship (where this was the relationship status before commencing the carer role) 1 , 2 , 3 providing care can have detrimental effects on the health and well‐being of care partners including emotional stress, physical strain, exhaustion, and loneliness. 4 , 5 , 6 These negative consequences of the caregiving role can lead to reduced focus on the care partner's own health, and increased risk of negative health outcomes, such as depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%